Penerapan Purse Lip Breathing Pada Pasien Asma Dengan Pola Nafas Tidak Efektif - Rizeki Dwi Fibriansari; Imania Shafa Camila Say; Zainal Abidin (Health and Technology Journal (HTechJ), 2025)
Asthma is a leading cause of global morbidity and mortality, accounting for 17.4% of deaths worldwide.  As one of the top 10 non-communicable diseases, asthma significantly impacts patients and their families.  Characterized by recurrent and reversible airway obstruction, asthma often leads to ineffective breathing patterns.  This study explored the impact of pursed-lip breathing (PLB) therapy on reducing respiratory rate in asthma patients with ineffective breathing patterns at Dr. Haryoto Hospital, Lumajang.  A case study design was employed from June 14 to June 18, 2024, involving a single asthma patient who met the criteria of dyspnea, abnormal breathing patterns, and the use of accessory respiratory muscles.  Data collection included objective and subjective measurements using observation sheets, physical examination tools, and standard operational procedures.  PLB therapy was administered over five days, with three daily sessions, each lasting 5 to 15 minutes.  The patient, presenting with symptoms such as shortness of breath, chest tightness, prolonged expiratory phase, and abnormal breathing patterns, showed significant improvements following PLB therapy.  Results indicated a reduction in respiratory rate by 6.76 breaths per minute, an increase in SpO2 by 3.44%, and a decrease in pulse rate by 51.62 beats per minute.  PLB therapy effectively reduced respiratory effort, alleviated dyspnea, enhanced oxygen transport, and strengthened respiratory muscles.  This study demonstrates that PLB therapy is an effective non-pharmacological intervention for managing asthma symptoms.  Nurses are encouraged to incorporate PLB therapy into patient education to empower asthma patients to manage their symptoms independently.